Age-Related Normogram for Ovarian Antral Follicle Count in Women with Polycystic Ovary Syndrome and Comparison with Age Matched Controls Using Magnetic Resonance Imaging - Senthil Kumar Aiyappan; Bulabai Karpagam; V. Vadanika; Prem Kumar Chidambaram; S. Vinayagam; K.C Saravanan (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Antral Follicle count (AFC) is a reliable marker for ovarian reserve. Previous studies have used transvaginal ultrasound for estimation of AFC, however we used magnetic resonance imaging (MRI) for estimation of AFC and for creating an age-related normogram in patients with polycystic ovary syndrome (PCOS) and compared it with normal patients. Aim: The aim of this study is to create an age related normogram for AFC in women with PCOS and to compare that with women without polycystic ovarian syndrome using MRI. Materials and Methods: A total of 1500 women were examined, out of which 400 fitted the criteria for PCOS. They all underwent MRI study and similar age matched women without PCOS also underwent MRI examination. Normogram for AFC were obtained using LMS software and a percentile chart was obtained. Results: Normogram for AFC in PCOS women showed decline in number of AFC as the age progresses and the decline was linear. The normogram for AFC was compared with equal number of patients without PCOS and they also showed decline in AFC as the age progresses, however the decline was exponential and faster. Conclusion: Age related normogram for AFC is widely used and considered as best clinical predictor for ovarian response in assisted reproductive technology. Knowledge of ovarian reserve is important in PCOS and non-PCOS females as PCOS patients are at risk for ovarian hyperstimulation syndrome during gonadotrophin theraphy. MRI is an equally effective and in some times better alternative to transvaginal ultrasound as it has got its own advantages.